Japan’s Efforts to Maintain its Presence in Indonesia through Popular Culture from 2011–2012 - Widarahesty, Yusy (WILAYAH: The International Journal of East Asian Studies, 2014)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.